Implementasi Pembelajaran Sains Berbasis Praktikum di Kelas V SD Inpres 48 Kabupaten Sorong - Icha Soraya; Indria Nur; Muhammad Ramli (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2025)
The problems discussed in this study are related to the implementation of science learning that focuses on practical work by using simple tools and materials to understand the learning outcomes of students about lava materials at SD Inpres 48 Sorong Regency. The focus of this research is to explore how to learn science practically using simple tools and materials. This research was carried out at SD Inpres 48 Sorong Regency and samples were taken from an affordable population, namely class V students totaling 38 people. This study uses a qualitative type of research, meaning that data collection is carried out directly at the research site, and the research method used is a qualitative method. This research was carried out in September 2024 and the results of the study showed that the average learning outcomes of students who participated in practical learning reached 90.2% higher than the average learning outcomes before practicum which was only 25.7%. It can be seen that practicum has a positive impact on students' understanding of lava materials